Pengaruh Waktu Kontak Terhadap Efektifitas Fitoremediasi Fosfat dan COD Dengan Eceng Gondok (Eichornia crassipes) dan Kiambang (Salvania natans) pada Limbah Cair Pencucian Pakaian - RD Muhammad Luthfi Firmansyah; Charles Situmorang (JURNAL TECHLINK, 2019)
The growth of the laundry industry in urban areas increasingly increases the level of pollution of urban water bodies by detergent waste so that water is increasingly polluted. One of the compounds contained in detergent is a phosphate compound which can cause eutrophication in water bodies. Phytoremediation is an attempt to use plants and their parts to decontaminate waste and environmental pollution problems. Eceng gondok (Eichhornia crassipes) and Kiambang (Salvania natans) is one of the water plants that can be used to reduce pollutant levels in industrial washing clothes waste by phytoremediation. This study aims to determine the ability of water hyacinth (Eichhornia crassipes) and kiambang (Salvania natans) in reducing phosphate in clothes washing waste by using two variables, namely the number of plants 2, 4 and 6 plants as well as contact time 2, 4 and 6 days. The results showed that the most optimum plants reduced phosphate levels, namely water hyacinth plants (Eichhornia crassipes) with 2 plants and 4 days contact time with a phosphate concentration of 0.3389 mg / L